THE CHARACTERISTICS OF MARINE PLANKTON AT AN INSHORE STATION IN THE GULF OF MANNAR NEAR MANDAPAM - Prasad, R Raghu (Indian Journal of Fisheries, 2016)
Study of the plankton of the inshore waters of the Gulf of Mannar was started in 1950 as a part of the programme of work carried out at the Central Marine Fisheries Research Station. As plankton forms directly or indirectly the food of fishes the primary object of this investigation is to get a general picture of the changes in the total plankton concentration, as indicated by fluctuations in the net-plankton volume, as well as the plankton compositidn and its relation to local fisheries.